ANALISIS PERSEPSI MASYARAKAT TERHADAP KUALITAS PELAYANAN PUBLIK PADA DINAS KEPENDUDUKAN DAN CATATAN SIPIL (DISDUKCAPIL) KABUPATEN BOGOR - Muchammad Hamdani; Mujito (Indonesian Journal of Social Science and Education (IJOSSE), 2025)
This study aims to determine the influence of public perception on the quality of public services at the Department of Population and Civil Registration (Disdukcapil) of Bogor Regency. The type of research used is descriptive quantitative. The population in this study consists of people who carried out administrative services at the Disdukcapil office of Bogor Regency, with a total sample of 100 respondents. Data analysis was conducted using the Weighted Means Score (WMS) method. The results of the study show that: (1) The highest average score from the analysis of public service quality indicators was the indicator related to “technical service requirements at Disdukcapil being easy to understand by the public,” which obtained an average value of 3.50, categorized as good. Another high indicator was “the completion of administrative processes at Disdukcapil on time,” with an average score of 3.55, also categorized as good. Meanwhile, the lowest average score was 3.19, categorized as fairly good, on indicators such as “the public feeling that their security is guaranteed when managing administrative services at Disdukcapil” and “service officers being disciplined in providing services to the community.” (2) The final recapitulation of the analysis across the ten main indicators of public service quality shows that the highest average score was found in the Certainty indicator, with a score of 3.48, categorized as fairly good. On the other hand, the lowest average scores were in the Discipline and Comfort indicators, both with scores of 3.23, also categorized as fairly good. (3) Overall, the average score of all public service quality indicators in this study was 3.34, categorized as fairly good. This indicates that, in general, the public perceives the quality of public services at the Disdukcapil of Bogor Regency to be fairly good. The recommendation given is that Disdukcapil Bogor Regency should further improve the discipline of its officers regarding their presence at the workplace or service counters, as well as their punctuality in serving the community, and also create a more comfortable environment and waiting area for the public accessing services.